Seckel syndrome: an overdiagnosed syndrome. Issue 3 (June 1985) - Thompson, E; Pembrey, M
Abstract : Five children in whom a diagnosis of Seckel syndrome had previously been made were re-examined in the genetic unit. One child had classical Seckel syndrome, a sib pair had the features of the syndrome with less severe short stature, and in two children the diagnosis was not confirmed. Seckel syndrome is only one of a group of low birth weight microcephalic dwarfism and careful attention should be paid to fulfillment of the major criteria defined by Seckel before the diagnosis is made. There remains a heterogeneous group of low birth weight microcephalic dwarfism yet to be defined.